CROSS CULTURAL CONFLICT RESOLUTION STYLES: DATA REVISITED - Nuray ALAGÖZLÜ (Informascope, 2017)
The way conflicts are solved is thought to be culturally learned (Hammer, 2005); therefore, this is reflected through language use. Conflicts, as inevitable parts of communication, naturally mirror cultural differences. Intercultural conflict styles have been studied so far by various researchers. How conflicts are initiated, maintained and escalated or terminated are all culture bound (Leung, 2002) and all the related stages vary from one culture to another. In the related literature, there have been attempts to describe different conflict handling classifications. Using Hammer's (2005) categorization that was found to be more refined and summative, conflict resolution styles of Turkish and American College students were explored using Discourse Completion Tests (DCT) with eight conflict situations where the respondents were required to write verbal solutions to overcome the conflicts described in the test. Those utterances were categorized according to Directness/Indirectness Scale modified from Hammer's (2005) "International Conflict Style Inventory (ICSI)" that classifies intercultural conflict resolution styles as high/low level of directness and high/low level of emotional expressiveness. It is believed that the study provides insight into intercultural communication as there are culturally generalizable (etic) and learned patterns of conflict resolution styles pertinent to different cultures (Hammer, 2009, p. 223; Ting-Toomey, 1994).